Predictive Biomarkers and Factors in Oral Squamous Cell Carcinoma: A Comprehensive Overview - Dave Rushang M.; Goswami Parth R.; Kateshiya Darshit L.; Belani Vaishali T.; Bhalodiya Nayana H. (Medical Research and Its Applications Vol. 2, 2024)
Oral squamous cell carcinoma (OSCC) is a type of cancer that arises from the squamous cells, which are the flat, thin cells that make up the lining of the mouth and throat. This cancer commonly affects areas such as the tongue, the floor of the mouth, and the inner lining of the cheeks, but it can occur anywhere in the oral cavity. It typically presents as a persistent sore or growth in the mouth that does not heal. Risk factors for OSCC include tobacco use, excessive alcohol consumption, human papillomavirus (HPV) infection, and prolonged exposure to sunlight (for lip cancer). Early detection and treatment are crucial for improving outcomes. The incidence rate of oral cancers, including OSCC, is reported to be around 20 per 100,000 people annually, making it a significant public health issue in India. This review consolidates the current understanding of prognostic markers for OSCC, providing insights into their clinical relevance and potential therapeutic implications. A thorough search of PubMed, Scopus, and Web of Science databases identified 30 highly cited articles, forming this review’s basis. Prognostic factors encompass tumor-related features, host factors, and molecular markers, each playing a crucial role in OSCC prognosis. Tumor size, lymph node involvement, histological grade, and depth of invasion are well-established predictors of patient outcomes. Additionally, biomarkers such as p53 mutations, EGFR overexpression, and altered miRNA profiles offer valuable insights into disease progression. Host factors, including age, gender, and lifestyle habits, also impact the prognosis. This review critically evaluates the evidence supporting these factors, highlighting their potential for personalized treatment strategies and improved patient care in OSCC.